Shear Bond Strength Of Two Calcium Silicate-Based Cements to Compomer - Burak Buldur; Fatih Öznurhan; Mevlüt Kayabaşı; Feride Şahin (Cumhuriyet University, 2018)
Objectives: The purposes of this in vitro study was to compare the bond strength of Biodentine® and Imicryl MTA to a compomer material, and to examine the effect of the setting time on the bond strength. Materials and Methods: A total of 100 acrylic blocks with a hole (4 mm in diameter and 2 mm in height) were prepared. Acrylic blocks were randomly divided into two main groups according to cement type to be applied, Biodontine® or Imicryl MTA (n = 50). The specimens of each main group were then divided into 5 subgroups, which were randomized relative to different setting times. (12 minutes, 24 hours, 48 hours, 72 hours, and 96 hours) (n = 10). The samples were filled completely with Biodentine® or Imicrly MTA according to the manufacturer's instructions. Compomer was placed in this transparent tube with the help of a hand plugger and light cured for 40 seconds with the LED device (EliparTM, 3M ESPE, MN, USA) to polymerize the compomer. The acrylic molds were fixed to a universal test machine and shear bond strength (SBS) test was made under shear force at a cross-speed of 1 mm/min. Data were analyzed by a two-way ANOVA and Tukey's post-hoc test (p=0.05). Results: While, Biodentine® had significantly higher SBS values than Imicrly MTA at 12m setting time (p<0.05), there was no difference between Biodentine® and Imicrly MTA among other setting periods (p>0.05). Regardless of cements tested, there were similar SBS values among pairwise comparisons between setting time groups (p>0.05). Conclusions: There were higher SBS values of Biodentine® to compomer than Imicrly MTA in all setting time groups, the only statistical significance existed in 12 min group. Keywords: Biodentine®, bond strength, calcium silicate-based cement, compomer